Beliefs in AI-Driven Language Learning Platforms Usage: Insights from Indonesian EFL Undergraduate Students - Rahmawati, Fithriyah (JOINT: Journal of Inspirational English Language Teaching, 2026)
This study investigates the beliefs of UIN Madura students regarding the use of AI-driven language learning platforms. It focused on three aspects: general beliefs about AI in language learning (particularly in English learning), its role in understanding literature, and its potential use in education in the future. Using a survey-based design, data were collected from students through a questionnaire comprising demographic details and Likert-scale questions addressing the three focal areas. The questionnaire was administered through Google Form during the odd semester of 2025 academic year. About 83 students have participated in the study. The findings reveal that students generally perceive AI as a beneficial tool for enhancing language learning. In literature, students appreciate AI’s ability to facilitate textual analysis but express reservations about its potential to inhibit critical thinking. Regarding future use, students are optimistic about AI’s role in advancing educational practices. The study underscores the importance of tailoring AI-driven educational tools to align with students’ beliefs and cultural contexts, promoting effective integration into language and literature learning.